IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE PRINCIPLES IN PT. AQUA GOLDEN MISSISSIPPI Tbk - Widisatria, Dymas (Dinasti Publisher, 2020)
This research was conducted at the largest bottled drinking water company (AMDK) in Indonesia. Implementation of the principles of Good Corporate Governance (GCG) in a good company include: Transparency, Accountability, Responsibility, Fairness, and Independence are effective as a tool for internal control of the company. So the company can supervise and ensure the performance of management can be controlled properly and lead to the achievement of increasing company value. The purpose of this study was to determine the implementation of the principles of Good Corporate Governance applied at PT. Aqua Golden Mississippi Tbk. This research is a qualitative research with a descriptive approach. The results of this study indicate that in practice PT. Aqua Golden Mississippi Tbk is not maximized in the running principles of Good Corporate Governance There are still many constraints on the implementation of Good Corporate Governance, including corporate organs that do not yet have independence, besides that law enforcement in Indonesia is still not firm, and there are still many KKN practices that are one of the obstacles to the enforcement of Good Corporate Governance.